Metamorphic Testing: Testing the Untestable - Segura, Sergio; Towey, Dave; Zhou, Zhi Quan; Chen, Tsong Yueh (IEEE software, 2020)
What if we could know that a program is buggy, even if we could not tell whether or not its observed output is correct? Metamorphic testing provides this ability. This article explains the basics of the technique.